Guided Discovery in Genetic Learning: Implementation and Impact on Higher-Level Thinking Skills - Fitri Laela Rahmadhani; Fuad Jaya Miharja; Atok Miftachul Hudha (Jurnal Pendidikan Biologi, 2021)
The challenges of 21st century education today require students to have high-level thinking skills given the many dynamic changes that occur in the field of education. High-level thinking skills are divided into several aspects including critical, creative and collaborative thinking skills. One of the appropriate learning model to improve critical thinking in students is the guided discovery model .The purpose of this study was to determine the implementation of  guided  discovery.  Model in learning genetics to increase higher thinking skills of students of SMAN 1 Lawang which include critical, creative, and collaborative thinking skills. This quasi-experiment was carried out by means of a pre-test and post-test control group design. The sample involved in this study is student of class XII IPA 3 (eksperiment class and student of class XII IPA 4 obtained by purposive sampling techniqueThe results showed that there are differences in the critical, creative and collaborative thinking skills of students who studied with the guided discovery model with a level of significance <0.05. The implementation of the guided discovery model can increase the level of critical, creative and collaborative thinking skills of students of SMAN 1 Lawang. This increase can be seen from the post test results of the experimental class, which are higher than the control class; the ability to analyze the results of the practicum that the experimental class has done; the creativity of students in processing and utilizing laboratory tools and materials; and the collaborative attitude of the students when participating in practicum activities.